Advanced integrated optical spectroscopy system for diamond anvil cell studies at GSECARS. Issue 3 (3rd July 2019) - Holtgrewe, Nicholas; Greenberg, Eran; Prescher, Clemens; Prakapenka, Vitali B.; Goncharov, Alexander F.
ABSTRACT: Raman and optical spectroscopy are versatile tools for nondestructive characterization of a wide range of properties of novel materials and minerals in situ at extreme and ambient conditions. These techniques are genuinely complementary to X-ray tools (diffraction and spectroscopy) in the probe energy, momentum transfer, and time scale, making concomitant X-ray and optical probes available for advanced sample analysis. We have built a state-of-the-art, user-friendly integrated Raman and optical spectroscopy system at Sector 13 (GeoSoilEnviroCARS, University of Chicago, IL) of the Advanced Photon Source (APS), Argonne National Laboratory (ANL), where optical probes are available now in combination with high resolution in-situ synchrotron X-ray diffraction and spectroscopy tools (XRD, IXS, XES, NFS, and others) for extensive sample investigation. The integrated optical system enables a variety of techniques including multi-colored (five laser lines: 266, 473, 532, 660, and 946 nm) confocal Raman, fluorescence, and optical spectroscopy from ultraviolet (UV) to near infrared (IR) spectral ranges (266–1600 nm), and Coherent Anti-Stokes Raman spectroscopy (CARS) in combination with near IR double sided laser heating.